2022
DOI: 10.1088/1361-665x/ac6a2f
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and experimental investigation of asymmetric distance with magnetic coupling based on galloping piezoelectric energy harvester

Abstract: This paper presents an asymmetric magnetic coupling piezoelectric energy harvester based on galloping to scavenge low-speed wind. The piezoelectric beam of energy harvester undergoes bending and torsional vibration simultaneously due to the eccentric distance. By analyzing the kinetic energy, potential energy, and virtual work of the energy harvesting system, the mathematical model of harvester is constructed and verified by experiments. The optimal external load resistance is confirmed at different eccentric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Although the energy resources of sea waves and water flows are abundant on Earth, they are usually restricted by geographical factors and are challenging to use fully. In contrast, the wind is the most widely distributed clean energy (Gong et al, 2020;Ma and Zhou, 2022;Ren et al, 2021;Zhang et al, 2017Zhang et al, , 2022b. It is thus of great significance to develop wind energy technology.…”
Section: Introductionmentioning
confidence: 99%
“…Although the energy resources of sea waves and water flows are abundant on Earth, they are usually restricted by geographical factors and are challenging to use fully. In contrast, the wind is the most widely distributed clean energy (Gong et al, 2020;Ma and Zhou, 2022;Ren et al, 2021;Zhang et al, 2017Zhang et al, , 2022b. It is thus of great significance to develop wind energy technology.…”
Section: Introductionmentioning
confidence: 99%
“…The study [19] focuses on improving the energy harvesting performance of galloping systems through the use of magnetic coupling. Conversely, the work [20] presents modeling and experimental investigations of asymmetric distances using magnetic coupling based on a galloping piezoelectric energy harvester, aiming to enhance the stability of the generated power. In the articles [21,22], it has been demonstrated that incorporating nonlinear stiffness into the system can significantly increase its efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [ 21 ] designed a wind energy harvesting device consisting of a cantilever beam and a flexible extension structure by imitating the oscillation of leaves in the wind, and they studied the effect of the fan and the T-shaped extension shapes on wind energy harvesting performance. Zhang et al [ 22 ] designed a galloping energy harvester with an asymmetric structure. The cantilever beam was not placed in the middle of the bluff body.…”
Section: Introductionmentioning
confidence: 99%